The factors that influence the transfer of training among academic staffs in Universiti Teknikal Malaysia Melaka (UTeM) / Melissa Roslan and Nurayuni Mahabib - Roslan, Melissa; Mahabib, Nurayuni (Faculty of Business and Management, 2015)
Transfer of training can be the one of the important elements in the training efficiency because it can boost up organization and employees performance level. Transfer of training can be influenced by many factors that can affect it from happening. The purpose of this study is to examine the instrumentality, learner readiness, peer support and supervisor support which identified could influence the transfer of training among academic staffs or lecturers. The primary data with sample size of 175 respondents have been collected through a set of questionnaire from academic staffs in engineering course at University Teknikal Malaysia Melaka (UTeM). Based on the analysis, found that instrumentality and leaner readiness has moderate positive relationship with transfer of training. Meanwhile, peer support and supervisor support has weak positive relationship with transfer of training. This study provides overview of the relationship between the factors that influence the transfer of training and the dominant factor in influencing a transfer of training.